1991
DOI: 10.1111/j.1755-3768.1991.tb04831.x
|View full text |Cite
|
Sign up to set email alerts
|

Work‐related penetrating eye injuries

Abstract: A review of all penetrating eye injuries treated at the Manchester Royal Eye Hospital over 5 years (January 1st 1982 to December 31st 1986) was undertaken. There were 258 penetrating eye injuries of which 69 (26.7%) were due to work-related accidents. All were men and 52 (75.4%) of them were under the age of 40 years. Hammering and chiselling were the commonest activities at the time of the injury and accounted for 25 cases (36.2%). Thirty-six patient (52.1%) had intraocular foreign bodies. Thirty-six patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…In our material, 38% of the PEI were occupational and were most common in construction work. This is in keeping with many other reports (Blomdahl & Norell 1984;Punnonen 1989;Pate1 & Morgan 1991). In Massachusetts (Schein et al 1988), 50% of all bulbar ruptures were caused by occupational traumas, half of them in construction industries and the other half in connection with automobile reparing units.…”
Section: Discussionsupporting
confidence: 88%
“…In our material, 38% of the PEI were occupational and were most common in construction work. This is in keeping with many other reports (Blomdahl & Norell 1984;Punnonen 1989;Pate1 & Morgan 1991). In Massachusetts (Schein et al 1988), 50% of all bulbar ruptures were caused by occupational traumas, half of them in construction industries and the other half in connection with automobile reparing units.…”
Section: Discussionsupporting
confidence: 88%
“…Foreign bodies especially consisting of small metal particles were the most common form of corneal foreign bodies. Patel and colleagues reported that 52% of intraocular foreign bodies that occur during hammering and chipping operations often at work have magnetic properties and that these cases constitute 26.7% of all penetrating eye injury cases 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Ocular trauma is a significant cause of unilateral blindness in Egypt [1], other Arab world countries [2][3][4][5][6][7], and even in developed countries [8][9][10][11][12][13][14][15][16]. However, a general survey of the incidence of ocular trauma and the resultant visual morbidity and blindness in Egypt has never been formally reported.…”
Section: Introductionmentioning
confidence: 99%